Investigating the effectiveness of Facebook marketing on firm competitiveness in the Real Estate Sector in Zimbabwe: A case of Trevor Dollar Real Estate. - Mashamba, Pauls T. (Midlands State University, 2017)
The main aim of this study was to investigate the effectiveness of Facebook marketing on firm competitiveness in the Real Estate Sector in Zimbabwe focusing on Trevor Dollar Real Estate Gweru Branch’s case. The objectives of the study were to ascertain the role of Facebook advertising on increasing company profit, to assess the importance of Facebook engagement on firm’s market share and to assess the influence of Facebook publicity on enhancing corporate image. Literature of Facebook marketing concept from authors, academics and field practitioners were reviewed revealing their points of convergence and their points of divergence. New insights, views and concepts were also added to enhance theoretical development in the field of Facebook marketing concept. Exploratory and descriptive research designs were used in this study. On drawing the sample size Krejcie and Morgan, (1970) model was used and 132 respondents were drawn from a target population of 200 people. The researcher used random sampling was used to select respondents from the Facebook fans cluster and judgmental sampling in the selection of managers focusing on the opinions and views of Trevor Dollar Real Estate’s Facebook fans and mangers on the effectiveness of Facebook marketing in rebuilding Trevor Dollar Real Estate’s competitiveness. Questionnaires were used to gather data from Facebook fans respondents and interviews for managers. The findings indicated that Facebook advertising can be effectively be used to increase profit of the company because of its reach, targeting facilities and it is cost effective. The results also revealed that Facebook engagement can enhance the firm’s market share by instilling loyalty in clients through one on one virtual interaction. Facebook publicity was found to be a viable strategy to enhance corporate image due to the fact that it is owner managed so the owner is at liberty to publish what the company wants without any delays. After the acquiring of findings the researcher concluded that Facebook marketing can effectively enhance firm’s competitiveness in the Real Estate Sector in Zimbabwe and therefore recommended Trevor Dollar Real Estate to adopt it so that they can improve their competitiveness.